2016
DOI: 10.1136/bmjopen-2016-012362
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of Pfizer-sponsored clinical trials: assessment of time to publication and publication history

Abstract: ObjectiveTo estimate the proportion of Pfizer-sponsored clinical trials that completed in 2010 and are published as manuscripts in the peer-reviewed literature, and to assess the manuscript development history.DesignRetrospective, cross-sectional analysis.SettingClinical trials registered in ClinicalTrials.gov that completed in 2010 for approved, Pfizer prescription products in patients or vaccines in healthy participants.Main outcome measuresThe proportion of studies for which the primary outcome(s) was publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…[5][6][7] Median times to publication were also consistent with previously published figures. [6][7][8][9] When we evaluated the impact of study outcome, first time acceptance rates for studies with positive outcomes were numerically, but not significantly, higher than for those with negative outcomes (56% v 48%). Median time from study completion to submission was 31 days longer for negative than for positive studies and time to publication was 102 days longer, suggesting that greater effort and care (such as journal selection) are required for publication of negative data.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[5][6][7] Median times to publication were also consistent with previously published figures. [6][7][8][9] When we evaluated the impact of study outcome, first time acceptance rates for studies with positive outcomes were numerically, but not significantly, higher than for those with negative outcomes (56% v 48%). Median time from study completion to submission was 31 days longer for negative than for positive studies and time to publication was 102 days longer, suggesting that greater effort and care (such as journal selection) are required for publication of negative data.…”
Section: Discussionmentioning
confidence: 94%
“…gov and other public sites were eventually published. [3][4][5][6][7][8][9] There has been wide variance across and within sponsor categories (such as industry, academia, government) and by study outcomes (presence versus absence of significance) in both publication rates as well as time to publication, with a general temporal trend toward increased disclosure rates. 3 4 6-12 Studies lacking statistically significant outcomes were less likely to be published and, when they were published, took a longer time from study completion to publication.…”
Section: Introductionmentioning
confidence: 99%
“…18 Some delays may be due to protracted peer review, which is no fault of the investigators. 19 Other delays outside the investigators' control are sponsor termination and contractual issues. 20 Publishing a protocol Publishing a protocol early increases transparency and gives the research community and the public a better idea of ongoing studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 85% (65/76) of Pfizer-sponsored clinical trials for approved products that completed in 2010 were published within 52 months of study completion. However more than 50% required submission to more than one journal to achieve publication, and 21% required three or more attempts 16 . A retrospective review of publication status by study outcome for all human drug research studies conducted by GlaxoSmithKline and completed between 1 January 2009 and 30 June 2014, of which 98% (1041/1064) had results posted on one or more public registries, reported that over 10% of all studies and 13% of those with negative outcomes required three or more submission attempts before they were accepted for publication in peer reviewed medical journals 17 .…”
Section: Discussionmentioning
confidence: 99%